Theories of Change and Mediators of Psychotherapy Effectiveness in Adolescents With Externalising Behaviours: A Systematic Review - Mestre, José M.; Taubner, Svenja; Mota, Catarina Pinheiro; Rangel Henriques, Margarida; Saliba, Andrea; Heinonen, Erkki; Ramos, Sara; Moreno-Peral, Patricia; Volkert, Jana; Adler, Asta; Barkauskiene, Rasa; Conejo-Cerón, Sonia; et al. (Frontiers in Psychiatry, 2022)
Background: Externalising behaviours are becoming a remarkably prevalent problem during adolescence. Psychological treatments aim to increase the social functioning of adolescents to live a more balanced life and prevent negative trajectories. However, little is known of the intervening variables and mediators involved in these treatments’ change mechanisms. We conducted a systematic review, exploring the available evidence on mediators of psychological treatments for externalising behaviours and symptoms amongst adolescents (10 to 19 years old). Methods: A systematic search was performed on Medline and PsycINFO databases, which identified studies from inception to 23rd February 2020. Eligible studies included randomised controlled trials that enrolled adolescents with externalising symptoms and behaviours as, at least, one of the primary outcomes. A group of 20 reviewers were divided into ten pairs. Each pair independently screened studies for inclusion extracted information and assessed the methodological quality of the included studies following Kazdin (2007) recommendations. The risk of bias of RCTs was assessed by the Mixed Methods Appraisal Tool (Hong et al., 2018). Extracted data from the included studies were reported using a narrative synthesis. Results: Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines (PRISMA), after removing duplicates, 3660 articles were screened. Disagreements were resolved by consensus. In a second stage, 965 full-text articles were assessed for eligibility. A total of 14 studies fulfilled all inclusion criteria. Two types of mediators were identified as potentially being involved in the mechanisms of change for better social-functioning of adolescents: to increase healthier parent-adolescent relationships and parental discipline. However, there were significant and non-significant results amongst the same mediators, which led to discussing the results tentatively. Conclusions: Family variables were found to be the largest group of investigated mediators, followed by relational, behavioural, and emotional variables. No cognitive nor treatment-specific mediators were identified. Adequate behavioural control of adolescents' peer behaviour and a better positive balance in their relationships with their parents seemed to buffer the effects of externalising behaviours in adolescents. Several methodological limitations concerning mediation testing design, outcome measures and mediators selection have been identified. Ethics and dissemination: Ethical approval was not required. PROSPERO registration number: CRD42021231835.